Short‐Course Blinatumomab Treatment as a Bridge to Further Salvage Therapy for Relapsed/Refractory B‐Cell Acute Lymphoblastic Leukemia: A Retrospective Single‐Center Study - Jin Yin; Xiaoya Cai; Bingxin Qian; Ying Liu; Dengju Li (Cancer Medicine)
ABSTRACT Backgroud The high cost of blinatumomab in full doses of full treatments has led to dose reduction and fewer treatment cycles for most patients in China. With current needs for cost‐efficiency and resource management in health care, we retrospectively evaluated the clinical effects of short‐course blinatumomab treatment for R/R Ph‐ B‐ALL at our center. Methods Blinatumomab was administered with 24‐h continuous intravenous infusion (9 μg/day for the first 3 days and 28 μg/day for 6–10 days). The clinical data of 30 R/R B‐ALL patients were collected and analyzed. Results A total of 25 patients (83.3%) including 13 (43.3%) with a high leukemic load (> 50%) achieved morphological CR. Twelve patients (40%) were MRD‐negative. The estimated 2‐year OS rate was 82.62%. The 2‐year PFS rate was 78.35%. The estimated 2‐year OS and PFS were significantly better in patients receiving further treatment. Conclusions Our findings provide novel insights into the optimization of blinatumomab therapy, proposing a viable treatment alternative that aligns with current needs for cost‐efficiency and resource management in health care.